Abatacept increases T cell exhaustion in early RA individuals who carry HLA risk alleles - Long, Sarah Alice; Muir, Virginia S.; Jones, Britta E.; Wall, Valerie Z.; Ylescupidez, Alyssa; Hocking, Anne M.; Pribitzer, Stephan; Thorpe, Jerill; Fuchs, Bryce; Wiedeman, Alice E.; Tatum, Megan; Lambert, Katharina; et al. (Frontiers in Immunology, 2024)
Exhausted CD8 T cells (TEX) are associated with worse outcome in cancer yet better outcome in autoimmunity. Building on our past findings of increased TIGIT + KLRG1 + TEX with teplizumab therapy in type 1 diabetes (T1D), in the absence of treatment we found that the frequency of TIGIT + KLRG1 + TEX is stable within an individual but differs across individuals in both T1D and healthy control (HC) cohorts. This TIGIT + KLRG1 + CD8 TEX population shares an exhaustionassociated EOMES gene signature in HC, T1D, rheumatoid arthritis (RA), and cancer subjects, expresses multiple inhibitory receptors, and is hyporesponsive in vitro, together suggesting coexpression of TIGIT and KLRG1 may broadly define human peripheral exhausted cells. In HC and RA subjects, lower levels of EOMES transcriptional modules and frequency of TIGIT + KLRG1 + TEX were associated with RA HLA risk alleles (DR0401, 0404, 0405, 0408, 1001) even when considering disease status and cytomegalovirus (CMV) seropositivity. Moreover, the frequency of TIGIT + KLRG1 + TEX was significantly increased in RA HLA risk but not non-risk subjects treated with abatacept (CTLA4Ig). The DR4 association and selective modulation with abatacept suggests that therapeutic modulation of TEX may be more effective in DR4 subjects and TEX may be indirectly influenced by cellular interactions that are blocked by abatacept.